Progress in Mathematics
DOI: 10.1007/0-8176-4467-9_16
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Calabi-Yau and Classical Crystals

Abstract: We propose a new duality involving topological strings in the limit of large string coupling constant. The dual is described in terms of a classical statistical mechanical model of crystal melting, where the temperature is inverse of the string coupling constant. The crystal is a discretization of the toric base of the Calabi-Yau with lattice length g s . As a strong evidence for this duality we recover the topological vertex in terms of the statistical mechanical probability distribution for crystal melting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
724
2
2

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 355 publications
(741 citation statements)
references
References 25 publications
13
724
2
2
Order By: Relevance
“…expression in terms of specialization of skew Schur functions [14]. Finally we prove (1.2) in section 4 by using the formulas for the specialization of skew Schur function.…”
Section: Introductionmentioning
confidence: 72%
“…expression in terms of specialization of skew Schur functions [14]. Finally we prove (1.2) in section 4 by using the formulas for the specialization of skew Schur function.…”
Section: Introductionmentioning
confidence: 72%
“…This defines the cubic topological vertex [42]. It is proportional to the combinatorial quantity Y q |Y| , where the sum runs over plane partitions Y whose edges in the three directions correspond to Young tableaux with the shapesR (a) [45]. Explicitly, the topological vertex amplitude in the canonical framing (2.33) is given by…”
Section: Toric Geometry and The Topological Vertexmentioning
confidence: 99%
“…In [3] it was shown that the target space formulation of the topological A-model on C 3 describes quantum foam on the same geometry. Remarkably, the partition sum of this model is identical to that of three dimensional crystal melting [4]. In two dimensions, crystal melting adds squares to a 2d Young tableau.…”
Section: Introductionmentioning
confidence: 71%
“…We caution that this material is more formal than other parts of this note. The A-model partition function on C 3 coincides with the crystal melting partition function [4]:…”
Section: Equivariant Sheaves and Topological Stringsmentioning
confidence: 98%
See 1 more Smart Citation